James Joyce and the art of mediation - Weir, David 1947- (Univ. of Michigan Press, 1996)
Beginning with an examination of Joyce's early critical writings and aesthetic speculations, Weir shows that the principles of mediation provides a common base for several well-known Joycean devices. The epiphany, for example, makes ordinary experience the medium for feeling and meaning, providing Joyce with a method of making high drama from everyday life. This early form of mediation serves as the model for later narrative developments, as Joyce begins to experiment with a number of devices that allow him to integrate logical, objective structures with psychological, subjective structures effects